2004
DOI: 10.1161/01.cir.0000140694.67251.9c
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Induces Heme Oxygenase-1

Abstract: Background-Evidence from experimental and clinical studies indicates that statins can protect the vessel wall through cholesterol-independent mechanisms. The "pleiotropic" effects include the prevention of inflammation and proliferation of vascular cells. Here, we studied whether heme oxygenase-1 (HO-1), an important cytoprotective molecule, is induced by simvastatin and the role of HO-1 in the pleiotropic effects of simvastatin. Methods and Results-Human and rat aortic smooth muscle cells treated with simvast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(103 citation statements)
references
References 34 publications
7
94
1
1
Order By: Relevance
“…Thus, recently four papers have been published in which the investigators reported the induction of HO-1 by statins [12]. In a study by Lee et al simvastatin, at the concentrations of 1-10 μM up-regulated HO-1 expression in human vascular smooth muscle cells, but, interestingly, neither in human macrophages nor in human umbilical vein endothelial cells (HUVEC) [13]. The effect of simvastatin was concentration dependent, and although the highest expression was attained at 10 μM, already at 1 μM of simvastatin HO-1 was induced.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, recently four papers have been published in which the investigators reported the induction of HO-1 by statins [12]. In a study by Lee et al simvastatin, at the concentrations of 1-10 μM up-regulated HO-1 expression in human vascular smooth muscle cells, but, interestingly, neither in human macrophages nor in human umbilical vein endothelial cells (HUVEC) [13]. The effect of simvastatin was concentration dependent, and although the highest expression was attained at 10 μM, already at 1 μM of simvastatin HO-1 was induced.…”
Section: Discussionmentioning
confidence: 99%
“…Statins also induce the expression of heme oxygenase-1 (HO-1) [88]. HO-1 is a stress-response protein, which is induced in response to UV radiation, cytokines and free radicals.…”
Section: Statins and Vascular Dysfunctionmentioning
confidence: 99%
“…Increased HO-1 expression reduces intimal thickening after arterial injury and attenuates atherosclerosis in apolipoprotein E deficient mice [8] . Moreover, increased activity of HO-1 inhibits proliferation of VSMCs [9][10][11] . Interestingly, it has recently been reported that HO-1 inhibits the proliferation of pancreatic stellate cells by repression of the ERK1/2 pathway [12] .…”
Section: Introductionmentioning
confidence: 99%